The impact of biogas power plant penetration on power system stability in the 20 kV distribution network of Tanjung Pura - Ashari, M.Juliansyah; Bintoro, Andik; Multazam, Teuku (Journal Geuthee of Engineering and Energy, 2025)
The penetration of biogas power plants into the distribution network can affect power system stability, particularly in the 20 kV distribution network in Tanjung Pura. This study aims to analyze the impact of biogas power plant penetration on voltage stability and power flow dynamics in the distribution network. A simulation-based approach using ETAP software is employed to evaluate different penetration levels, ranging from low to high. The results indicate that biogas power plant (PLTBg) penetration increases system voltage from the existing 17.92 kV (89.63%) to 18.34 kV (91.73%) at 25% penetration and reaches 19.50 kV (97.50%) at 100% penetration. Under a load increase of 25% to 75%, the voltage without penetration ranges from 17.56 kV (87.80%) to 17.05 kV (85.30%). With gradual penetration, the voltage rises to 17.99 kV (90%)–17.28 kV (86.40%) at 25% penetration and reaches 19.15 kV (95.40%)–18.47 kV (92.30%) at 75% penetration. Additionally, higher PLTBg penetration reduces active power losses but increases reactive power losses, which could compromise network stability if not properly compensated. The optimal condition is observed at 50% loading with 75% penetration, where voltage remains within normal limits while both active and reactive power losses are more stable compared to other scenarios.